Isolation and Characterization of Cell Envelope Fragments Comprising Archaeal S-Layer Proteins - Kevin Pfeifer; Eva-Kathrin Ehmoser; Simon K.-M. R. Rittmann; Christa Schleper; Dietmar Pum; Uwe B. Sleytr; Bernhard Schuster (Nanomaterials, 2022)
The outermost component of cell envelopes of most bacteria and almost all archaea comprise a protein lattice, which is termed Surface (S-)layer. The S-layer lattice constitutes a highly porous structure with regularly arranged pores in the nm-range. Some archaea thrive in extreme milieus, thus producing highly stable S-layer protein lattices that aid in protecting the organisms. In the present study, fragments of the cell envelope from the hyperthermophilic acidophilic archaeon Saccharolobus solfataricus P2 (SSO) have been isolated by two different methods and characterized. The organization of the fragments and the molecular sieving properties have been elucidated by transmission electron microscopy and by determining the retention efficiency of proteins varying in size, respectively. The porosity of the archaeal S-layer fragments was determined to be 45%. S-layer fragments of SSO showed a retention efficiency of up to 100% for proteins having a molecular mass of ≥ 66 kDa. Moreover, the extraction costs for SSO fragments have been reduced by more than 80% compared to conventional methods, which makes the use of these archaeal S-layer material economically attractive.